Digital finance platform: Synergy between accounting applications and modern tax systems - Nugraha, Yongky Rangga Yuda; Nurdina, Hana (Educoretax, 2025)
This study explores the convergence of management information systems, digital accounting applications, and electronic taxation platforms in build-ing an integrated financial ecosystem through a quantitative approach in-volving two hundred and fifty organizations in Indonesia using purposive sampling techniques. The Partial Least Square-Structural Equation Model-ing analysis revealed that the integration architecture is based on five fun-damental layers covering infrastructure, data, application, business process, and presentation layer with the adoption of API-based integration in eighty-two percent of respondents resulting in a significant increase in op-erational efficiency and business process automation. Top management support with a score of four point eight, adequate budget allocation of four point six, and the competence of the IT team four point five collectively ex-plain the sixty-two percent variance of implementation success, while re-sistance to change with severity of four point seven and legacy system complexity of four point five are the main barriers faced by organizations. The findings confirm that the transformation of the digital financial ecosys-tem requires the synergy of technological dimensions, business processes, and organizational change management to achieve sustainable competitive advantage in the digital economy era.